Lactate metabolism and lactylation in cardiovascular disease: novel mechanisms and therapeutic targets - Zhang, Han; Zhao, Jiulu; Yu, Jizhang; Zhang, Xi; Ran, Shuan; Wang, Song; Ye, Weicong; Luo, Zilong; Li, Xiaohan; Hao, Yanglin; Zong, Junjie; Li, Ran; et al. (Frontiers in Cardiovascular Medicine, 2024)
Cardiovascular disease (CVD) is responsible for approximately 30% of annual global mortality rates, yet existing treatments for this condition are considered less than ideal. Despite being previously overlooked, lactate, a byproduct of glycolysis, is now acknowledged for its crucial role in the cellular functions of the cardiovascular system. Recent studies have shown that lactate influences the proliferation, differentiation, and activation of immune cells through its modulation of post-translational protein modifications, thereby affecting the development and prognosis of cardiovascular disease. Consequently, there has been a notable increase in interest towards drug targets targeting lactylation in immune cells, prompting further exploration. In light of the swift advancements in this domain, this review article is dedicated to examining lactylation in cardiovascular disease and potential drug targets for regulating lactylation, with the aim of enhancing comprehension of this intricate field.